2013
DOI: 10.1007/s11427-013-4483-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of iodoacetic acid induced photoreceptor degeneration in the cat

Abstract: Iodoacetic acid (IAA) has been applied to different species to acutely induce photoreceptor degeneration. The purpose of the present study was to use this toxin to thoroughly eliminate photoreceptors and induce complete blindness in the cat. IAA was delivered by single ear vein injection (20 mg kg 1 ). Six months after the IAA treatment, functional evaluations including pupillary light reflex (PLR), electroretinogram (ERG), visual behavior tests were performed. Morphological examinations were carried out afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…3,7 Different behavioral tests, which were based on the ability to avoid obstacles, were used to assess vision in the IAA cat model and in the transgenic pig model of photoreceptor degeneration. 11,17 In both cases, animals were not trained, and the efficacy of the test varied between animals regardless of their vision status. In our current study, the OC test was designed to include a 2-wk training period to accustom the animals to the trial environment, including new smells and noises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7 Different behavioral tests, which were based on the ability to avoid obstacles, were used to assess vision in the IAA cat model and in the transgenic pig model of photoreceptor degeneration. 11,17 In both cases, animals were not trained, and the efficacy of the test varied between animals regardless of their vision status. In our current study, the OC test was designed to include a 2-wk training period to accustom the animals to the trial environment, including new smells and noises.…”
Section: Discussionmentioning
confidence: 99%
“…OC test. Nine pigs treated with IAA and 5 control animals were evaluated by using a previously described behavioral test 17 with specific modifications. The pigs enrolled in the test were divided into 3 groups (Table 1), to facilitate their management.…”
Section: Behavioral Assessment Of Vision In Pigsmentioning
confidence: 99%
“…Another cat model, the CrxRdy cats, develops retinal thinning that initially takes place in the central retina [ 159 ]. An acute, reliable, and complete photoreceptor degeneration model in cats can be achieved by ear vein injection of high-dose iodoacetic acid [ 161 ]. Retinal sheet transplantation studies conducted in Abyssinian cats showed good signs of transplant integration with the host retina and lamination of transplant photoreceptors.…”
Section: Animal Models For Stem Cell-based Therapiesmentioning
confidence: 99%
“…Among animal models, the eyes of felines and swine have a central region (comprised partly of photoreceptors) comparable to the human macula, with similar distributions of rod and cone cells in the central and peripheral retina [9]. Therefore, using iodoacetic acid (IAA), such animals have been designated as models of retinal degeneration [101112131415]. IAA reacts with the sulfhydryl groups of glyceraldehyde 3-phosphate dehydrogenase (GADPH) in cells of various organs, including the eye, and inhibits anaerobic glycolysis [161718192021].…”
mentioning
confidence: 99%
“…In this process, the inner retina is preserved and shows histological features that appear early in human RP [22]. Based on these characteristic findings of retinal degeneration, an animal model of IAA-induced retinal degeneration has been designed to explore effective treatment of RP disease in human eyes [101214].…”
mentioning
confidence: 99%